2010
DOI: 10.1128/aac.01176-09
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Pharmacology of the Anti-Hepatitis B Virus Agent β- l -2′,3′-Didehydro-2′,3′-Dideoxy-N 4 -Hydroxycytidine: Relevance for Activation in HepG2 Cells

Abstract: A large number of nucleoside analogues have been described as inhibitors of hepatitis B virus (HBV) and HIV replication. Recently L-nucleoside analogues in particular have gained increasing interest. They are characterized by an opposite configuration from that of the natural D-nucleoside analogues and represent one of the most attractive groups of antiretroviral compounds, including ß-L-2Ј,3Ј-dideoxy-3-thiacytidine (3TC) and its, and ß-L-2Ј,3Ј-didehydro-2Ј,3Ј-dideoxy-2Ј-fluoro-cytidine (L-2ЈFd4C) (3,5,22).Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In 2010, Matthes et al , have investigated and reported β‐L‐2′,3′‐didehydro‐2′,3′‐dideoxy‐N 4 ‐Hydroxycytidine 45 as potent inhibitor of HBV virus in HepG2 cells (Figure 35). [72] The biological evaluation results showed that compound 45 had moderately potent antiviral activity and lowers cytotoxicity of HBV replication against HepG2 cells to 5’‐triphosphate in cells with 50 % Effective dose (ED 50 ) of 0.03 μM.…”
Section: Inhibitory Activities Of Cytidine Derivativesmentioning
confidence: 99%
“…In 2010, Matthes et al , have investigated and reported β‐L‐2′,3′‐didehydro‐2′,3′‐dideoxy‐N 4 ‐Hydroxycytidine 45 as potent inhibitor of HBV virus in HepG2 cells (Figure 35). [72] The biological evaluation results showed that compound 45 had moderately potent antiviral activity and lowers cytotoxicity of HBV replication against HepG2 cells to 5’‐triphosphate in cells with 50 % Effective dose (ED 50 ) of 0.03 μM.…”
Section: Inhibitory Activities Of Cytidine Derivativesmentioning
confidence: 99%
“…Beyond ribavirin, ribonucleoside analogs present an exciting option for the discovery of broad-spectrum lyssavirus inhibitors. For instance, the ribonucleoside analogy N 4hydroxycytidine reportedly blocks both seasonal and pathogenic influenza virus strains, respiratory syncytial virus, Ebola virus, chikungunya virus, and hepatitis B and C viruses [182][183][184][185][186][187][188] with excellent pharmacological properties [182]. If antiviral activity equally extends to RABV and related lyssaviruses, compounds like N 4 -hydroxycytidine may present an example for a viable next-generation therapeutic option to address the rabies challenge.…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…Recently we described the hydroxylation of the amino group of some of these l-deoxycytidine analogue-produced compounds, which maintained their strong anti-HBV activity but exhibited markedly reduced cytotoxicity [6]. The most effective compound was b-l-2′,3′didehydro-2′,3′-dideoxy-N 4 -hydroxcytidine (l-Hyd4C; 50% effective dose in HepG2.2.15 cells 0.03 mM and 50% cytotoxic dose in HepG2 cells 2,500 mM) [6,7]. For the first in vivo study of this new group of compounds, a 5-fluoromodified derivative of the l-Hyd4C, the b-l-2′,3′-didehydro-2′,3′-dideoxy-N 4 -5fluorocytidine (l-Hyd4FC) predicting the most favourable pharmacokinetic properties was selected.…”
Section: Original Articlementioning
confidence: 99%
“…To establish HBV infection in mice, human chimeric mice received a single intraperitoneal injection of mouse-derived HBV-positive serum (2×10 7 HBV DNA copies, genotype D, hepatitis B e antigen [HBeAg]-positive). Only mice that had been infected with HBV for ≥10 weeks and hence displayed stable viraemia levels of >10 7 HBV DNA copies/ml were used for the study.…”
Section: Hbv Infection and Antiviral Treatmentmentioning
confidence: 99%
See 1 more Smart Citation